Vibrational circular dichroism and chiroptical properties of chiral Ir(iii) luminescent complexes12. Issue 3 (9th December 2015) - Mazzeo, Giuseppe; Fusè, Marco; Longhi, Giovanna; Rimoldi, Isabella; Cesarotti, Edoardo; Crispini, Alessandra; Abbate, Sergio
Abstract : Three chiroptical spectroscopic techniques are applied to an octahedral iridium complex. The vibrational exciton interpretation of VCD spectra is especially important. Abstract : The octahedral ionic Ir(iii ) complex with a dual stereogenic centre of general formula Δ, Λ-( R, S )-[(ppy)2 Ir(Me-Campy)]X, where ppy = 2-phenylpyridine and Me-Campy = 2-methyl-5, 6, 7, 8-tetrahydroquinolin-8-amine, and the complex Λ-( R, S )-[(ppy)2 Ir(H-Campy)]X, where ppy = 2-phenylpyridine, H-Campy = 8-amino-5, 6, 7, 8-tetrahydroquinolines and X − = Cl − as a counterion in both cases, have been characterized by vibrational circular dichroism (VCD), which turns out to be efficacious in diastereomeric discrimination. Moreover, the single crystal X-ray structure of the complex Δ-( R )-[(ppy)2 Ir(Me-Campy)]Cl is reported here. Density functional theory (DFT) calculations allow us to conclude that the most important doublet feature in the VCD spectra is associated with a clear vibrational exciton structure located on the two dissymmetrically disposed phenylpyridine ligands. The features in the VCD spectra associated with the ( R ) or ( S )-central chirality configuration are identified and commented on. DFT calculations provide also the interpretation of electronic circular dichroism (ECD) spectra. Finally, circularly polarized luminescence (CPL) spectra are presented as an additional chiroptical characterization of these luminescent iridium complexes.